Successful treatment of fusarium solani ecthyma gangrenosum in a patient affected by leukocyte adhesion deficiency type 1 with granulocytes transfusions - Mellouli, Fethi (BioMed Central, 2010)
BACKGROUND: Ecthyma gangrenosum (EG) manifests as a skin lesion affecting patients suffering extreme neutropenia and is commonly associated with Pseudomonas aeruginosa in immunocompromised patients. Leukocyte adhesion deficiency I (LAD I) which count among primary immunodeficiency syndromes of the innate immunity, is an autosomal recessive disorder characterized in its severe phenotype by a complete defect in CD18 expression on neutrophils, delayed cord separation, chronic skin ulcers mainly due to recurrent bacterial and fungal infections, leucocytosis with high numbers of circulating neutrophils and an accumulation of abnormally low number of neutrophils at sites of infection. CASE PRESENTATION: We report at our knowledge the first case of a child affected by LAD-1, who experienced during her disease course a multi-bacterial and fungal EG lesion caused by fusarium solani. Despite targeted antibiotics and anti-fungi therapy, the lesion extended for as long as 18 months and only massive granulocytes pockets transfusions in association with G-CSF had the capacity to cure this lesion. CONCLUSION: We propose that granulocytes pockets transfusions will be beneficial to heal EG especially in severely immunocompromised patients.